Pierwsze dendrodaty z białogardzkiego grodziska - Cnotliwy, Eugeniusz (Folia Praehistorica Posnaniensia, 2018)
Settlement phases of the Białogard stronghold, excavated in the years 1970-1972, have been dated by pottery typology so far. These dates, in particular those from the earliest phases, have been recently questioned. Twelve wooden samples from well preserved wooden constructions from the sixth phase of the stronghold fortification were taken in 1991 from a section of the former trench. The following dates of truncation were obtained: 878-892 and 902/903 AD. Pottery chronology of the sixth phase gave 25 years older dates. There are still no precise dates from the earliest phases of occupation.